1995
DOI: 10.1351/pac199567071117
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of the stability constants of metal complexes of amino acids with polar side chains (Technical Report)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(170 citation statements)
references
References 28 publications
13
149
0
7
Order By: Relevance
“…где Кд -константа диссоциации лейцина равная 2,4 [12]. С помощью математических преобразо-ваний из формулы (5) получено квадратное уравнение вида α 2 + 2,4α -2,4 = 0 (6) С учётом того, что α не может быть отрица-тельной величиной, из двух корней квадратного уравнения был выбран корень, равный 0,9611.…”
Section: +unclassified
“…где Кд -константа диссоциации лейцина равная 2,4 [12]. С помощью математических преобразо-ваний из формулы (5) получено квадратное уравнение вида α 2 + 2,4α -2,4 = 0 (6) С учётом того, что α не может быть отрица-тельной величиной, из двух корней квадратного уравнения был выбран корень, равный 0,9611.…”
Section: +unclassified
“…The major reasons for this are: (i) Cu(I) is readily oxidised or, as noted above, disproportionates to Cu(II) in aqueous media in the absence of suitable complexing agents; 22 (ii) both the thioamino acids and their complexes are also readily oxidised; (iii) sparingly soluble precipitates are formed over wide pH ranges (especially with cysteine and glutathione); and (iv) all of these systems show pronounced tendencies to form protonated and polynuclear complexes. 23 In spite of these difficulties the biological relevance of the Cu(I) complexes of these particular thioamino acids has motivated many attempts to characterize them. Unfortunately, however, there is little agreement about the stoichiometry of the species formed, let alone their formation constants (see, e.g., Refs.…”
Section: ): (R)-2-amino-3-sulfhydrylpropanoic Acid (L-cysteine Hs-chmentioning
confidence: 99%
“…The tendency of CSH to form protonated and polynuclear complexes with a variety of metal ions is well known. 23 Interestingly, Bagiyan et al 46 indicated that protonated complexes of Cu(CS)  formed readily during their pH-metric titrations but only reported a value for  110 (Table 5). 28 Consistent with the present findings, Harman and Sóvágó 49 have pointed out that the degree of formation and stoichiometry of M n+ PSH polynuclear complexes should be markedly different from those for M n+ CSH due to steric inhibition by the -methyl substituents in the former.…”
Section: Also Included Inmentioning
confidence: 99%
“…4 interaction of the organotin moieties with several biologically relevant compounds such as carbohydrates, amino acids, peptides, nucleic acids and DNA has been carried out mostly in the last decade [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. From some of these cited studies, the interaction of dimethyltin (IV) and trialkyltin(IV) (with R = methylic, ethylic, and butylic groups) in aqueous solution, at physiological pH, with thiol groups of model molecules, as well as feline and rat haemoglobin, have been investigated by 119 Sn Mössbauer spectroscopy.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In particular, no calorimetric study has been performed. The , Hg 2+ and others, but there are no enthalpic data on tin or alkyltin cations [21].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%